Transforming Challenges into Opportunities: The Journey of the University Towards Environmental Based Budgeting - Taufik Kurrohman; Farida Wahyu Ningtyias; Siska Aprilia Oktaviani (Jurnal Reviu Akuntansi dan Keuangan, 2025)
Purpose: This research scrutinizes the impact of the COVID-19 pandemic on the progress towards achieving a sustainable campus, with a specific focus on carbon emissions in higher education institutions. It aims to provide an in-depth understanding of the challenges and adaptations faced by universities during the pandemic, using the University of Jember in Indonesia as a case study. Methodology/approach: The study employs a case study methodology, centering on the University of Jember as the subject of analysis. Carbon emissions are quantitatively assessed through an economic valuation of the university's budget, which is then converted using specific parameters. The research meticulously examines the alterations in campus operations induced by the pandemic, encompassing changes in work procedures and financial expenditures. Findings: The findings reveal a paradoxical scenario where there is an increase in carbon emissions from non-medical waste. However, a noteworthy reduction of 13.5% in overall carbon emissions was observed when comparing the averages before and during the COVID-19 pandemic. These results underscore the complex interplay between operational adjustments and environmental impact during the pandemic period. This study contributes to the existing body of knowledge by offering empirical evidence on the environmental impact of the COVID-19 pandemic on university operations, particularly in the context of carbon emissions. Practical implications: It provides valuable insights and potential strategies for other universities worldwide, aiming to adapt and align their operations with sustainable development goals amidst unforeseen challenges.   Originality/value: The unique context of the University of Jember adds a novel dimension to the discourse on sustainability in higher education institutions during global crises.